Risk of the Development of Fibrosis in Metabolic Dysfunction-Associated Fatty Liver Disease in Patients with Rheumatoid Arthritis - Murat Aydın; Berrin Aksakal; Sema Basat (İstanbul Medical Journal, 2023)

(untitled)
Introduction: Individuals diagnosed with rheumatoid arthritis (RA) face a heightened risk of developing metabolic dysfunction-associated fatty liver disease (MAFLD). The primary objective of this study was to examine the progression of hepatic fibrosis through non-invasive tests in patients with MAFLD, both those with RA and those without RA. Methods: In our retrospective study, a total of 120 MAFLD patients aged between 18 and 65 years, excluding those with juvenile RA, were included. Patients were divided into two main groups as patients with (n=60) and without (control group, n=60) RA. Fibrosis-4 (FIB-4) and NAFLD Fibrosis Score (NFS) (NAFLD/MAFLD fibrosis) scores were used to determine the risk of hepatic fibrosis in patients with MAFLD. These scores were compared between the two groups. The relationship between FIB-4 and NFS scores and other parameters was evaluated. SPSS 25.0 software was used for statistical analysis, and significance was accepted as p<0.05. Results: The RA group exhibited a higher NFS value than the control group (p<0.05). Receiver operating characteristic analysis indicated that NFS, although relatively weak, could be considered a viable variable for diagnosis (p<0.05). Notably, a statistically significant correlation was identified between the FIB-4 score and several other factors, including age, estimated-glomerular filtration rate, platelet (PLT) count, and aspartate aminotransferase values (p<0.001; r=0.860). Similarly, a statistically significant correlation was found between the NFS score and factors such as age (p<0.001), albumin (p<0.001), PLT count (p<0.001), and alanine aminotransferase values (p<0.05) (r=0.956). Conclusion: Our study highlights that patients with both MAFLD and RA face a heightened risk of fibrosis progression compared with those without RA. While existing literature acknowledges MAFLD’s association with liver fibrosis, there is a scarcity of research on RA’s influence in this context. Our findings emphasize RA as an additional risk factor for liver fibrosis, particularly among patients with MAFLD. Consequently, liver fibrosis is more prevalent in patients with MAFLD and RA.